2022
DOI: 10.3389/fmars.2022.1022375
|View full text |Cite
|
Sign up to set email alerts
|

The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing

Abstract: Details of the chlorophyll-a (Chl-a) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl-a inversion model was built using in-situ Chl-a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl-a concentration and fish resources were revealed. The results show that: (1) High Chl-a concentration area was mainly concentrated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…In-fa induced Ekman pumping significantly contributed to the rise in SSS, while rainstorms and changes in currents efficiently decreased SSS; this is a phenomenon that has also been observed in other nearshore seas [33,58,61] Previous studies [46,62,63] have shown that Chl-a concentrations are higher in the coastal area of Zhoushan Fishery in summer (Figure 6(a1,a2)), which is probably due to the rich nutrients carried by the Yangtze diluted water, coastal upwelling, and sufficient sunlight. The maximum Ch1-a concentration usually occurs at the surface or subsurface layers, and the concentration decreases with depth [62].…”
Section: The Mechanism Of Typhoon Effect On Chl-amentioning
confidence: 54%
See 3 more Smart Citations
“…In-fa induced Ekman pumping significantly contributed to the rise in SSS, while rainstorms and changes in currents efficiently decreased SSS; this is a phenomenon that has also been observed in other nearshore seas [33,58,61] Previous studies [46,62,63] have shown that Chl-a concentrations are higher in the coastal area of Zhoushan Fishery in summer (Figure 6(a1,a2)), which is probably due to the rich nutrients carried by the Yangtze diluted water, coastal upwelling, and sufficient sunlight. The maximum Ch1-a concentration usually occurs at the surface or subsurface layers, and the concentration decreases with depth [62].…”
Section: The Mechanism Of Typhoon Effect On Chl-amentioning
confidence: 54%
“…Previous studies [46,62,63] have shown that Chl-a concentrations are higher in the coastal area of Zhoushan Fishery in summer (Figure 6(a1,a2)), which is probably due to the rich nutrients carried by the Yangtze diluted water, coastal upwelling, and sufficient sunlight. The maximum Ch1-a concentration usually occurs at the surface or subsurface layers, and the concentration decreases with depth [62].…”
Section: The Mechanism Of Typhoon Effect On Chl-amentioning
confidence: 76%
See 2 more Smart Citations
“…The models were evaluated using R 2 and adj-R 2 values (Table 1), showing the best-fit models under different independent variable inputs. The results indicated that the model had a significant response to the blue (Rrs_483) and red (Rrs_613, Rrs_655) bands of Landsat imagery, which are also commonly used to establish statistical relationships with the Chl-a and TSM concentrations [36][37][38]. Therefore, the model can explain the impact of SST on the DO concentration and reflects the relationships among the Chl-a, TSM, and DO concentrations to a certain extent, offering good interpretability and practical significance.…”
Section: Model Validationmentioning
confidence: 91%